Plasticità deflagrate. "Alla cieca" di Claudio Magris (Comparatismi, 2025)
This paper aims to analyze Alla cieca (2005) by Claudio Magris as a work that radically and irreducibly questions the status of the novel form. Far from being a historical novel in the traditional sense, Alla cieca weaves together autobiography, epic, clinical report, myth, and essayistic writing into a palimpsestic and polyvocal structure. As a result, the narrative unfolds as a “novel-mixtape” and “novel-mashup,” in which heterogeneous fragments – from classical mythology to historical documents – are superimposed and rewritten, in the name of a conscious hybridization that destabilizes the boundaries of genres and produces a text that continually makes and unmakes itself. Through this fluidity, Claudio Magris destabilizes the very notion of genre as a fixed category, transforming it into a dynamic energy in constant tension between memory and invention. Alla cieca thus becomes the laboratory of a “protean novel,” where the dialogue among genres is an integral part of the representation of History and of the metaliterary reflection on writing.
Keywords: Alla cieca; Claudio Magris; Literary genre; Metatextuality; Novel